Dataset: Cross-contamination risks in sediment-based resurrection studies of phytoplankton - Andersson, Björn; Rengefors, Karin; Kourtchenko, Olga; Johannesson, Kerstin; Berglund, Olof; Filipsson, Helena L (University of Gothenburg, 2022)
The data contains sediment core measurements from two locations in the Baltic Sea. The aim of the study was to determine if the age of phytoplankton resting stages could be determined based on their vertical position or if contamination from surface population was a major confounding factor. To this end, the concentration of seven abundant species of diatoms and cyanobacteria were enumerated using the Most Probable Number (MPN) approach. Sediment sections were dated using standard radiometric methods, and surface sediment contamination was quantified using 4.5 μm microsphere tracers. Furthermore, ex-situ longevity was monitored over four years and decreased substantially withing this timeframe. In the cores, microspheres (>2×10^-6 fractions) were translocated from the sediment surface and could well explain the vertical distributions and abundances of viable cells (between ~106 to <0.8 g sediment^-1). Our conclusion was therefore that there are substantial contamination risks, and that age determination of resting stages using only radiometric age determination of bulk sediment is flawed without additional contamination controls.
The study design consisted of two field expeditions (2017 and 2020) where six to ten, 50 cm cores were collected. Cores were inspected for signs of damage and preservation of laminated patterns, and the best cores were selected for further analysis. Selected cores were section onboard for bulk radiometric dating (210Pb and 137Cs) and Total Organic Carbon (TOC) and Nitrogen (TN) profiles. MPN enumeration of diatom and cyanobacterial resting stages was performed on cores transported intact to Gothenburg, which were processed within two to six months (reported as initial concentration). Survival ex-situ was monitored from 2017 to 2021 in surface samples stored under dark, cold (4C), and anoxic conditions, in 20-40 mL of sediment in 50 mL non-transparent Falcon tubes. To assess the validity of the radiometric age determination of diatoms from 2017, we quantified contamination during the 2020 sampling. Non-toxic, yellow-green fluorescing polystyrene microspheres (Thermo Scientific™ Fluoro-Max) were used to track surface sediment contamination in three VG20 cores. Microspheres were injected into the water headspace of three replicate cores (in Gothenburg) and allowed to settle onto the surface before sectioning. The translocation of microsphere from the sediment surface could then be traced in tandem with enumeration of resting stages.
See file Metadata_Andersson2022.docx for a detailed description of files and data.

Datasetet innehåller geologiska och biologiska observationer från två svenska Östersjö-fjärdar. Det innehåller isotopiska dateringsdata och andra standardiserade geologiska parametrar, samt kvantifiering av vertikaldistributionen av vilostadier av växtplankton, främst kiselalger och cyanobakterier. Utöver detta kvantifierades kontaminering mellan sedimentdjupen med hjälp av fluorescerande 4,5 μm mikroplastkulor.

Läs filen Metadata_Andersson2022.docx för detaljerad information om filer och datainsamling.
Dataset: Kontamineringsrisker vid sediment-baserat återupplivande av växtplankton
Keywords: phytoplankton; fytoplankton; Geology; Geologi; Sea regions; Havsområden; Species distribution; Arters utbredning; radiometric dating; isotopdatering; Contamination; Kontaminering; sediment cores; sedimentkärnor; longevity; överlevnad; resting stages; vilostadier; Environmental Sciences; Miljövetenskap; Geology; Geologi; Microbiology; Mikrobiologi; Ecology; Ekologi; Biota; Biologi och ekologi; Geoscientific Information; Geovetenskap; Oceans; Kust och hav